2012
DOI: 10.1177/0954008312439082
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of polyacrylonitrile doped PVDF/heteropoly acid composite membranes

Abstract: A novel polyacrylonitrile (PAN)/phosphotungstic acid (PWA) doped PVDF composite membrane was successfully prepared by blending electrospinning. Impedance spectroscopy and scanning electron microscopy characterization showed that the electrospun composite membranes possess comparatively higher proton conductivity and well-defined microstructure. In particular, the addition of hydrophilic PAN can effectively improve the water uptake performance of composite membrane and simultaneously no obvious membrane swellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…The FTIR spectra showed a dramatic reduction in the absorption at 2243 cm À1 (shifted to 2239 cm À1 because of the conjugation effect), coupling with the increase of 1615 cm À1 . These two peaks are assigned to stretching of nitrile group and C¼N, respectively, 28 which indicates that the cyclization occurs extensively. The significant decrease in CH 2 bending signal at 1450 cm À1 and the increase of C¼C stretching signal at 1580 cm À1 confirm that the dehydrogenation happened in a large part of the chain, 29,30 which results in the formation of aromatic ring structure.…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR spectra showed a dramatic reduction in the absorption at 2243 cm À1 (shifted to 2239 cm À1 because of the conjugation effect), coupling with the increase of 1615 cm À1 . These two peaks are assigned to stretching of nitrile group and C¼N, respectively, 28 which indicates that the cyclization occurs extensively. The significant decrease in CH 2 bending signal at 1450 cm À1 and the increase of C¼C stretching signal at 1580 cm À1 confirm that the dehydrogenation happened in a large part of the chain, 29,30 which results in the formation of aromatic ring structure.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in figure 1(a), after the pre-oxidation treatment, the stretching vibration peaks of -C≡N (2240 cm −1 ) in nitrogen and air atmospheres were significantly weakened, while the variations of -C=N and -C=C vibration peaks located at 1620 cm −1 and 1580 cm −1 indicated the reaction formation structures significantly increased. It was revealed that cyclization and dehydrogenation [31] occurred in the above two atmospheres. At the same time, C=O peak represented the carboxyl group in the comonomer and appeared at 1730 cm −1 in the PAN copolymer before the pre-oxidation treatment.…”
Section: Conjugated Structures Of Pre-oxidized Pan At Different Ambie...mentioning
confidence: 99%
“…The strongest peak of the α phase is stated to be 766 cm À1 . [64][65][66][67][68][69][70][71][72][73][74] As a result of all of this, crystalline phase analyses and crystalline phase percentages were investigated in the presented study using FTIR measurements FTIR analyses were conducted for each sample to specify the degree of crystallinity of the β phase content. Figure 8 shows the FTIR spectrum of each electrospun PVDF and PVDF/BaTiO 3 nanofibers.…”
Section: Ftir Analysismentioning
confidence: 99%